Institutional Governance and Service Excellence in Higher Education: A Public Administration Perspective - Andy Chairuddin; Wahira Wahira; Suarlin Suarlin; Andi Aslinda; A. Kasmawati; Andi Cudai Nur (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
The growing demand for transparency, accountability, and measurable performance has transformed higher education institutions into complex public organizations required to deliver reliable and stakeholder-oriented services. Within this governance-driven environment, institutional governance plays a fundamental role in shaping service excellence and institutional legitimacy. Drawing on a public administration perspective, this study examines how governance dimensions influence academic service performance in higher education. This research employs a qualitative descriptive-analytical design. Data were collected through in-depth interviews, document analysis, and institutional observations involving university leaders, academic administrators, faculty members, and students. The analysis focuses on governance dimensions—transparency, accountability, participation, effectiveness, and responsibility—and their integration into institutional systems such as performance management, quality assurance, and digital infrastructure. The findings reveal that governance frameworks are formally established through regulations and digital systems; however, their operational integration remains uneven. Transparency improves service reliability when supported by consistent information management, while accountability mechanisms tend to emphasize procedural compliance rather than performance-based evaluation. Stakeholder participation is institutionalized but largely consultative. The study concludes that service excellence in higher education is a governance-driven outcome that requires systemic alignment between governance principles, institutional capacity, and performance management processes. Strengthened governance integration enhances service reliability and institutional legitimacy.